Effects of gibberellic acid concentration and fruit maturation stage on seed germination and vigor of pitahaya seedlings - Santos, T. P. [UNESP]; Sá, M. E. [UNESP]; Malagutti, E. S. [UNESP]; Pinto, M. S. [UNESP]; Ferreira, A. F. A.; Monteiro, L. N. H. [UNESP]; Silva, A. C. C.; Soutello, R. V. G. [UNESP]; Rodrigues, M. G. F. [UNESP] (Instituto Internacional de Ecologia, 2022)
With increased interest in cultivation, the study of white-fleshed pitahaya (Selenicereus undatus (Haw.) D.R. Hunt, Cactaceae family) seedling production is of fundamental importance in the search for novel techniques to increase cultivation and guarantee homogeneous and productive orchards. The present study investigated the influence of various gibberellic acid (GA3) concentrations and fruit maturation stages on seed germination and vigor of white-fleshed pitahaya seedlings, considering the physiological quality of seedlings produced to support genetic breeding and conservation programs of the species. White-fleshed pitahaya seeds at two maturation stages (physiologically ripe and maintained at 10 °C in Biochemical Oxygen Demand incubators for three months) were treated with varying GA3 concentrations of 0, 50, 100, and 500 mg/L. We observed the influence of fruit storage on seedling germination, emergence, and growth as a function of GA3 concentration. According to the results, seeds extracted from ripe white-fleshed pitahaya fruits grown under the conditions tested here required GA3 application to increase seedling emergence and vigor, with optimal doses in the 150–300-mg/L range. In the case of pitahaya fruits intended for storage for future seed removal and maintained under the same sowing conditions, the application of higher doses of GA3 was necessary when compared to the previous condition, with a minimum dose of 500 mg/L GA3. The present study shows that the maturation stage of white-fleshed pitahaya fruits intended for seed removal influences the quality of seedlings; therefore, the use of seeds extracted from ripe pitahaya fruits without fermentation is more appropriate for the purpose.

Com o crescente interesse no seu cultivo, estudos na produção de pitaya ((Selenicereus undatus (Haw.) D.R. Hunt, família Cactaceae) é de fundamental importância quando se busca novas técnicas para o incremento do cultivo e garantia de um pomar homogêneo e produtivo. Objetivou-se avaliar a influência do uso de diferentes concentrações de ácido giberélico e do estágio de maturação de frutos na germinação de sementes e vigor de plântulas de pitaya vermelha da polpa branca, tendo em vista a qualidade fisiológica de mudas produzidas a fim de subsidiar trabalhos de melhoramento genético e conservação da espécie. Foram utilizadas sementes de frutos de pitaya vermelha da polpa branca em dois estágios de maturação (fisiologicamente maduros e conservados à 10°C em BOD por 3 meses), tratadas com diferentes concentrações de ácido giberélico: 0, 50, 100 e 500 mg/L. Foi possível observar que houve influência do armazenamento de frutos na germinação, emergência e crescimento das plântulas em função das concentrações de ácido giberélico. Assim, verifica-se que, no caso de sementes extraídas de frutos maduros de pitaya vermelha da polpa branca, quando semeadas nas condições do presente estudo, é necessário a utilização de GA3 para incrementar a emergência e o vigor das plântulas, com doses ótimas variando entre 150 e 300 mg/L. No caso da necessidade em armazenar os frutos de pitaya para a posterior retirada de sementes, também nas mesmas condições de semeadura do presente estudo, observa-se que, em síntese, é necessária a utilização de GA3, porém em doses maiores do que o observado no primeiro, sendo de, no mínimo, 500 mg/L. O presente estudo mostra que há influência do estágio de maturação dos frutos de pitaya vermelha de polpa branca para retirada de sementes sobre a qualidade das mudas, concluindo que o uso de sementes extraídas de frutos maduros, sem fermentação, é mais adequado para esta finalidade.
Doses de ácido giberélico e estágio de maturação de frutos na germinação de sementes e vigor de plântulas de pitaya
Keywords: Selenicereus undatus (Haw.) D.R. Hunt; white-fleshed pitahaya; fruit storage; growth regulator; seedling production; Selenicereus undatus (Haw.) D.R. Hunt; pitaia vermelha de polpa branca; armazenamento de frutos; regulador de crescimento; produção de mudas